118k views
4 votes
y = c_1e^x + c_2e^-x is a two-parameter family of solutions of the second-order DE y'' - y = 0. Find a solution of the second-order IVP consisting of this differential equation and the given initial conditions. 11. y(0) = 1, y'(0) = 2 12. y(1) = 0, y'(1) = e 13. y(-1) = 5, y'(-1) = -5 14. y(0) = 0, y'(0) = 0

User Aygul
by
6.3k points

1 Answer

3 votes

Answer:

11)y =
(3)/(2) e^(x) - (1)/(2) e^(-x)

12)y =
(e^(2) )/(1+e^(2) ) (e^(x) - e^(-x) )

13)y =
5e^(-(x+1))

14)y = 0

Explanation:

Given data:


y=c_(1) e^(x) +c_(2) e^(-x)

y''-y=0

The equation is


m^(r)-1 = 0

(m-1)(m+1) = 0

if above equation is zero then either

m - 1 = 0 or m + 1 = 0

m = 1 , m = - 1

11)

y(0) = 1 , y'(0) = 2


y'=c_(1) e^(x) -c_(2) e^(-x)


c_(1) +
c_(2) = 1 (y(0) = 1) (1)


c_(1) -
c_(2) = 2 (y'(0) = 2) (2)

adding 1 & 2

2
c_(1) = 3


c_(1) = 3/2

3/2 +
c_(2) = 1


c_(2) = 1 - 3/2


c_(2) = - 1/2

y =
(3)/(2) e^(x) - (1)/(2) e^(-x)

12)

y(0) = 1 , y'(0) = e


c_(1) +
c_(2) = 0 (y(0) = 1) (3)


c_(1) = -
c_(2)


e=c_(1) e -c_(2) e^(-1) (y'(0) = 2) (4)


e=c_(1) e -(c_(2) )/(e) }


e =(c_(1) e^(2) -c_(2) )/(e) }


e^(2) ={c_(1) e^(2) -c_(2) }

replace
c_(2) =
c_(1) by equation 3


e^(2) ={c_(1) e^(2) -c_(1) }

taking common
c_(1)


e^(2) =c_(1) ({e^(2) -1 })


\frac{e^(2) }{({e^(2) -1 })} =c_(1)


-\frac{e^(2) }{({e^(2) -1 })} =c_(2)

y =
(e^(2) )/(1+e^(2) ) (e^(x) - e^(-x) )

13)

y(-1) = 5 , y'(-1) = -5


c_(1)
e^(-1) +
c_(2)
e^(1) = 5 (y(-1) = 5 ) (5)


c_(1)
e^(-1) -
c_(2)
e^(1) = -5 (y'(-1) = -5) (6)

Adding 5&6

2
c_(1)
e^(-1) = 0


c_(1) = 0


c_(2)
e^(1) = 5 -
c_(1)
e^(-1)


c_(2)
e^(1) = 5 - 0


c_(2)= 5/e

y =
5e^(-1) e^(-x)

y =
5e^(-(x+1))

14)

y(0) = 0 , y'(0) = 0


c_(1) +
c_(2) = 0 (y(0) = 0) (7)


c_(1) -
c_(2) = 0 (y'(0) = 0) (8)

Adding 7 & 8

2
c_(1) = 0


c_(2) =

y = 0

User Jot Dhaliwal
by
5.9k points